Reconceptualizing TQM in service ecosystems: an integrated framework. Issue 1 (24th October 2018) - Polese, Francesco; Vesci, Massimiliano; Troisi, Orlando; Grimaldi, Mara
Abstract : Purpose: The purpose of this paper is to reconceptualize Total Quality Management (TQM) in the light of service ecosystem view through the identification of dimensions underlying both the approaches and a clarification of the relationship between the two theories. Design/methodology/approach: An overview on service ecosystems and on TQM is conducted, with particular focus on the main dimensions of the two frameworks derived from extant research. Consequently, an assessment of the key features of both theories is performed. Findings: The work identifies four recurring dimensions in TQM, suggesting their rereading in the light of the assessed five recurring dimensions of service ecosystem. Moreover, a reconceptualization of TQM in the light of service ecosystem view is proposed. Originality/value: This paper compares and proposes an integration between TQM and service ecosystem view. Such a reinterpretation of "traditional" view of quality management in the light of current trend of Service-Dominant (S-D) logic can represent a starting point for further research aimed at analysing the mechanisms underlying joint production of value in service delivery.